Affective complementarity in service encounters - Angelo Giardini; Michael Frese (Management Revue, 2007)
Face-to-face interactions are a crucial part of services. However, research that investigates the dynamics of service encounters is still rare. In this study we used a theoretical framework that aligned the concept of interpersonal complementarity with Mehrabian and Russell's (1974) three-dimensional model of affect. We hypothesized that there are positive relationships between employees' and customers' affective experience of pleasantness and arousal (correspondence rule) and a negative relationship between the interactants' experience of power (reciprocity rule). Furthermore, we explored the role of gender combination in service encounters. We tested our hypotheses with a sample of 29 service employees and 345 service encounters. Using hierarchical linear modeling (HLM), our hypotheses were confirmed. Furthermore, we found that the relationship between employee and customer arousal was affected by the gender combination.
Keywords: 650; emotions; service; social Interaction; Dienstleistungsqualität; Kundenzufriedenheit; Soziale Beziehungen; Emotion